HEAT TRANSFER RATE OF SINTERED ZEOLITE WICK HEAT PIPE - Luh Putu Ike Midiani; I Nyoman Suprapta Winaya; Wayan Nata Septiadi; Made Sucipta (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2020)
This paper discusses about heat transfer rate in heat pipe with sintered zeolite wick. The type of zeolite is natural zeolite and activated zeolite. Zeolite used in powder form divided into two grain size i.e. 100 µm and 200 µm. Wick were made by sintering process. Calculation of the heat transfer rate for sintered zeolite heat pipe shows sintered zeolite activates heat pipe has the highest heat transfer rate.